Molecular diversity and pathogenicity of Ralstonia solanacearum species complex associated with bacterial wilt of potato in Rwanda - Sharma, K.; Kreuze, Jan F.; Abdurahman, A.; Parker, M.; Nduwayezu, A.; Rukundo, P. (Scientific Societies, 2020)
Bacterial wilt (BW), caused by Ralstonia solanacearum species complex (RSSC), leads to substantial potato yield losses in Rwanda. Studies were conducted to (i) determine the molecular diversity of RSSC strains associated with BW of potato, (ii) generate a RSSC distribution map for epidemiological inferences, and (iii) test the pathogenicity of predominant RSSC phylotypes on six commercial potato cultivars. Surveys were conducted in 2018 and 2019, tubers from wilting potato plants were collected for pathogen isolation. DNA was extracted from 95 presumptive RSSC strain colonies. The pathogen was phylotyped by multiplex PCR and typed at sequevar level. Phylotype II sequevar 1 strains were then haplotyped using multilocus tandem repeat sequence typing (TRST) schemes. Pathogenicity of one phylotype II strain and two phylotype III strains were tested on cultivars Kinigi, Kirundo, Victoria, Kazeneza, Twihaze and Cruza. Two RSSC phylotypes were identified, phylotype II (95.79%, n = 91) and phylotype III (4.21%, n = 4). This is the first report of phylotype III strains from Rwanda. Phylotype II strains were identified as sequevar 1 and distributed across potato growing regions in the country. The TRST scheme identified 14 TRST haplotypes within the phylotype II sequevar 1 strains with moderate diversity index (HGDI = 0.55). Mapping of TRST haplotypes revealed that a single TRST ‘8-5-12-7-5’ haplotype plays an important epidemiological role in BW of potato in Rwanda. None of the cultivars had complete resistance to the tested phylotypes, level of susceptibility varied among cultivars. Cultivar Cruza, which is less susceptible to phylotype II and III strains, is recommended when planting potatoes in the fields with history of BW.